PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE ( TPS ) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 011 BUKIT KAPUR - Alpusari, Mahmud Alpusari Mahmud; ', Efrida; ', Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study is based on the results of the low third-grade students learn science SDN 011 Bukit Kapur Dumai. Average science student learning outcomes at the beginning of the data was 70.09. The design of this study was classroom action research that aims to improve the learning outcomes of third-grade students of SDN 011 Bukit kapur by applying the learning model of type kooperatis Think Pair Share (TPS). The research was conducted in April 2014. Subjek this study was third grade students of SDN 011 Bukit kapur school year 2013/2014 the number of students 32. Average student learning outcomes in daily test cycle I was 77.65 and 81.40 in the second cycle increases. Classical completeness of students on daily test cycle I 56.25% and increased the daily test II to 90.62% classically been completed. For all teachers in the first cycle the first meeting is 66.66%. and the first cycle of the second meeting be 87.50%. In the second cycle is 100% the first meeting and the second meeting of the second cycle remains 100%. For a student activity meeting the first cycle I is 70.83% and the second meeting of the first cycle increased to 83.33%. At the first meeting of the second cycle increased 87.5% and the second meeting on the second cycle increases to 100%. From these results it can be concluded that the application of cooperative learning model Think Pair Share (TPS) can improve the learning outcomes of third-grade students of SDN 011 Bukit kapur. Keywords: Cooperative Learning Model Type Think Pair Share (TPS), Learning Outcomes.